An Attack Detection Mechanism Based on a Distributed Hierarchical Multi-agent Architecture for Protecting Databases - Pinzón Trejos, Cristian; De Paz, Yanira; Cano, Rosa; Rubio, Manuel (My University, 2009)
This paper presents an innovative approach to detect and classify SQL injection attacks. The existing approaches are centralized while this proposal is based on a distributed hierarchical architecture to provide a robust and dynamic strategy. The strategy for the classification and detection of SQL injection attacks uses a combination based on detection by anomalies and misuses. The detection by anomaly uses a case-based reasoning mechanism incorporating a mixture of neural networks. The approach has been tested and the results are presented in this paper.
This paper presents an innovative approach to detect and classify SQL injection attacks. The existing approaches are centralized while this proposal is based on a distributed hierarchical architecture to provide a robust and dynamic strategy. The strategy for the classification and detection of SQL injection attacks uses a combination based on detection by anomalies and misuses. The detection by anomaly uses a case-based reasoning mechanism incorporating a mixture of neural networks. The approach has been tested and the results are presented in this paper.
Keywords: SQL injection; Security database; IDS; Multi-agent; Case-based reasoning; SQL injection; Security database; IDS; Multi-agent; Case-based reasoning